Answer:
x = -7
Explanation:
Solve for x:
2 x + 3 = x - 4
Hint: | Move terms with x to the left-hand side.
Subtract x from both sides:
(2 x - x) + 3 = (x - x) - 4
Hint: | Combine like terms in 2 x - x.
2 x - x = x:
x + 3 = (x - x) - 4
Hint: | Look for the difference of two identical terms.
x - x = 0:
x + 3 = -4
Hint: | Isolate terms with x to the left hand side.
Subtract 3 from both sides:
x + (3 - 3) = -3 - 4
Hint: | Look for the difference of two identical terms.
3 - 3 = 0:
x = -3 - 4
Hint: | Evaluate -3 - 4.
-3 - 4 = -7:
Answer: x = -7